Impact of Parasites and Parasitic Diseases on Animal Health and Productivity - Muriu, Jian (Journal of Animal Health, 2023)
Purpose: The aim of the study is to investigate the impact of parasites and parasitic diseases on animal health and productivity. Methodology: This study adopted a desktop methodology. This study used secondary data from which include review of existing literature from already published studies and reports that was easily accessed through online journals and libraries Findings: The study found that parasites and parasitic diseases have a significant impact on animal health and productivity across various species. Negative associations between parasitic infections and key indicators of health and productivity, such as weight gain, milk production, reproductive performance, wool quality, and egg quality. Animals with higher parasite burdens tend to experience slower growth rates, reduced fertility, compromised immune function, and increased susceptibility to other diseases. Additionally, parasitic infections can lead to poor feed conversion ratios, higher mortality rates, and decreased overall productivity in livestock and poultry farming operations Unique Contribution to Theory, Practice and Policy: The study was anchored on Resource Competition Theory which was proposed by Robert M. May in 1974 and Immunopathology Theory which was proposed by Zinkernagel and Doherty in 1974. The study recommends that Governments and regulatory bodies should develop and enforce policies that promote responsible parasite control practices in livestock production.